Get Answers to all your Questions

header-bg qa

q4) Factorise 

iii)

 x ^4 - ( y + z )^4

Answers (1)

best_answer

We have,
             x ^4 - ( y + z )^4 =
                                           (x^{2})^{2} -((y+z)^{2})^{2} = (x^{2} - (y+z)^{2})(x^{2} +(y+z)^{2})\\ \Rightarrow (x-(y+z))(x+(y+z))(x^{2} +(y+z)^{2})
                                                                                                                                       (using \ a^{2} -b^{2} = (a-b)(a+b))
                 

Posted by

Gautam harsolia

View full answer